Differences in Viewpoints Between East and West in the Evolution of MACROECONOMIC Theories - Rosa Sanjayyana, Adzka; Kurniawati, Yuyun (EKOBIMA, 2023)
This article discusses mixed finance or Financial Blended which is always a topic every year in the Finance Track of the G20 Summit. Financial Blended has a crucial role in overcoming the infrastructure gap in countries, especially the member countries of the G20 Summit and generally globally. Initially the discussion on Financial Blended was not highly prioritized, but since the 12th G20 Summit in 2017 in Hamburg, Germany, the topic of Financial Blended has become a prioritized topic because infrastructure gaps are increasingly evident. From year to year, funds are disbursed either free of charge or loans to related countries, be it from the IMF, MDB, DFI, or philanthropic institutions. With the existence of this Finance Blended, the results are slowly but surely starting to be seen and it is considered to be quite effective in dealing with infrastructure gaps. This can be proven by several infrastructures that have succeeded in inviting investors and various other benefits for countries that implement Financial Blended in their infrastructure development.